Role of upper respiratory tract fibroscopy in patients with cervical lymph node metastases from squamous-cell carcinoma without the primary tumor found - M. A. Krylovetskaya; I. G. Komarov; A. Yu. Kontsevaya; O. A. Malikhova (Опухоли головы и шеи)
Background. The detection of primary tumor in patients with cervical lymph node metastases without the primary tumor found is very important, because its location often determines the treatment strategy. The study objective is to analyze the capabilities of upper respiratory tract fibroscopy for the detection of primary tumor in patients with cervical lymph node metastases from squamous-cell carcinoma without the primary tumor found.Materials in methods. A total of 70 patients with cervical lymph node metastases without the primary tumor found, in whom cytological examination of biopsy specimens collected from cervical lymph nodes revealed squamous-cell carcinoma, underwent upper respiratory tract fibroscopy in N.N. Blokhin National Medical Research Center of Oncology between January 2017 and May 2020.Results. In 24 out of 70 patients, fibroscopy helped to identify the primary tumor and collect biomaterial for morphological examination. Twelve patients were found to have oropharyngeal cancer; ten patients were diagnosed with nasopharyngeal cancer; and 2 patients had laryngopharyngeal cancer. Fifteen out of 24 patients had tumors less than 1.2 cm.Conclusion. Upper respiratory tract fibroscopy is a highly effective method for detecting small asymptomatic tumors. It can be recommended for the examination of patients with metastases from squamous-cell carcinoma without the primary tumor found, if the primary tumor is believed to be located in the upper respiratory tract